2011
DOI: 10.1080/14786411003781515
|View full text |Cite
|
Sign up to set email alerts
|

Antihistaminic and antiviral activities of steroids ofTurbinaria conoides

Abstract: The steroids 3,6,17-trihydroxy-stigmasta-4,7,24(28)-triene (A) and 14,15,18,20-diepoxyturbinarin (B) were isolated from the cyclohexane extract of brown alga, Turbinaria conoides (J. Agardh) Kutzing, and have been reported for their antimicrobial activity by us. In this study, the isolated compounds were evaluated for comprehensive antihistaminic, antiviral and cytotoxicity screening. The antihistaminic study was performed using in vitro standard animal models. Evaluation of the potency (EC(50)), affinity (pA(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Fucosterol ( 3 ) has been reported to show anti-oxidant and hepatoprotective activities in rats [ 64 ]. In addition, antihistaminic, anticholinergic, and antiviral activities have been described for fucosterol isolated from T. conoides (J. Agardh) Kutzing [ 65 ]. Saringosterol ( 7 ) has been identified as active principle in the extract of Lessonia nigrescens for the inhibition of Mycobacterium tuberculosis [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fucosterol ( 3 ) has been reported to show anti-oxidant and hepatoprotective activities in rats [ 64 ]. In addition, antihistaminic, anticholinergic, and antiviral activities have been described for fucosterol isolated from T. conoides (J. Agardh) Kutzing [ 65 ]. Saringosterol ( 7 ) has been identified as active principle in the extract of Lessonia nigrescens for the inhibition of Mycobacterium tuberculosis [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial and antiviral activity has also been reported for polyphenolic compounds derived from brown algae (Phaeophyta) such as Sargassum wightii and Turbinaria ornata [7], and fucosterol from Turbinaria sp. [8,9]. It has been shown that antibacterial activity in macroalgae can be caused by the presence of sulphate polysaccharides (SPs) produced by the seaweeds themselves [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rumput laut sangat bermanfaat misalnya di bidang kesehatan, enzimologi, dan mikrobiologi (La Barre et al, 2010). Selain itu, rumput laut juga berpotensi sebagai antitumor (Fajarningsih et al,2008), antibakteri (Kantida et al, 2012), antifungi (Kumar et al, 2010), antivirus (Kumar et al, 2009), antifouling (Kantida et al, 2012) dan antioksidan Vijayabakar and Shiyamala (2012).…”
Section: Pendahuluanunclassified